Critical coupling for chiral symmetry breaking in QCD motivated models - Aguilar, A. C. [UNESP]; Natale, A. A. [UNESP]; Rosenfeld, Rogério [UNESP] (American Physical Society (APS), 2000)
We determine the critical coupling constant above which dynamical chiral symmetry breaking occurs in a class of QCD motivated models where the gluon propagator has an enhanced infrared behavior. Using methods of bifurcation theory we find that the critical value of the coupling constant is always smaller than the one obtained for QCD. ©2000 The American Physical Society.